2022
DOI: 10.1002/admi.202200879
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Races of Binary Colloids with Different Softness at the Air/Water Interface of Sessile Droplets

Abstract: drying phenomena are ubiquitous not only in the laboratory environment, but also in our daily lives.So far, substantial theoretical and experimental effort has been devoted to controlling the drying behavior of colloidal dispersions. For instance, the formation of coffee-ring stains can be suppressed by using various additives or anisotropic particles, as well as by modifying substrates, [3c,4] which leads to various applications including surface coating, ink-jet printing, and chemical/biological sensors. [5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In this context, our group has investigated the selforganization of microgels and soft deformable particles during the evaporation of water from sessile droplets. [40][41][42][43][44][45][46] Microgels spontaneously adsorb and gradually order at the air/water interface of a dilute dispersion droplet, whereby the center-to-center distances of the microgels decrease due to the decrease in the interfacial area. 40 Furthermore, the ordered structures of the microgel monolayers that are formed at the air/water interface remain on a solid substrate after evaporation.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, our group has investigated the selforganization of microgels and soft deformable particles during the evaporation of water from sessile droplets. [40][41][42][43][44][45][46] Microgels spontaneously adsorb and gradually order at the air/water interface of a dilute dispersion droplet, whereby the center-to-center distances of the microgels decrease due to the decrease in the interfacial area. 40 Furthermore, the ordered structures of the microgel monolayers that are formed at the air/water interface remain on a solid substrate after evaporation.…”
Section: Introductionmentioning
confidence: 99%
“…Soft microgel particles based on poly(Nisopropylacrylamide) (p-NIPAM) are known to adsorb onto air/ water interfaces of drops. [15][16][17] Moreover, polyelectrolyte microgels, 18 binary mixture of soft and softer microgels 19 and rodshaped microgels 20 are also found to adsorb onto the air/water interface. Unlike a pure water drop or a drop dispersed with hard colloidal particles, a soft microgel particle laden drop stays pinned even on a hydrophobic surface for almost the entire duration of evaporation.…”
Section: Introductionmentioning
confidence: 99%
“…11 To date, a considerable amount of research has been dedicated to understanding phenomena related to the deformation of microgels at fluid interfaces. 11,12 In our group, we have investigated the drying behavior of sessile droplets that contain various soft particles, including microgels, 13 and found that deformed microgels at the air/water interface become more regularly arranged over time, whereby the center-to-center distances of the microgels decrease. 11 b ,13 c This process results in the compression of the deformed microgels at the air/water interfaces, and thus the microgels are further deformed at the interface as the surface area of the sessile droplets decreases.…”
mentioning
confidence: 99%